Efectividad de un programa para el aprendizaje de la decodificación lectora en niños de una institución educativa de Ventanilla - Callao - Castillo Durand, Bacilia Elena (2011)
The main purpose of this study is to show the effectiveness of learning phonics in reading decoding, by designing and implementing a pilot program based on the systematization of the method to which we refer, starting from the theoretical model cognitive psychology and psycholinguistics. We worked with a sample of 50 students from first grade elementary. In order to assess their level of reading decoding they were exposed to a specific dyslexia exploration test, obtaining from this evaluation the significant differences between the level of reading decoding of students exposed to the experimental program versus those who were not taught with this method, concluding that the phonetic style program has favorable implications for the learning of reading decoding.